Charge Disproportionation and Magnetoresistivity in a Double Perovskite with Alternate Fe4+(d4) and Mn4+(d3) Layers. Issue 15 (10th April 2014) - Ganesanpotti, Subodh; Tassel, Cédric; Hayashi, Naoaki; Goto, Yoshihiro; Bouilly, Guillaume; Yajima, Takeshi; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract: An oxygen‐stoichiometric, B‐site‐ordered perovskite Ca2 Fe1.1 Mn0.9 O6 (CFMO) with alternate stacking of Fe and Mn layers was obtained through topochemical oxidation of the corresponding brownmillerite phase under high pressure in the presence of KClO4 . The structure crystallizes in the P 21 / m space group with a doubling of the cell along all three crystallographic axes. Mössbauer spectroscopy, susceptibility, and resistivity measurements suggest ferromagnetic interactions between Fe 4+ (d 4 ) and Mn 4+ (d 3 ) along [001] through a double‐exchange mechanism, a situation similar to half‐doped manganese perovskite oxides. Upon cooling, CFMO exhibits a ferrimagnetic transition below T c = 90 K, likely accompanied by a charge disproportionation of the iron site, 2Fe 4+  → Fe 3+ + Fe 5+ . A reasonably good magnetoresistivity of 27 % was observed below T c . Abstract : High‐pressure oxygen intercalation of a brownmillerite phase Ca2 Fe1.1 Mn0.9 O5 provides a fully oxidized layered double perovskite Ca2 Fe1.1 Mn0.9 O6 with alternate Fe 4+ (d 4 ) and Mn 4+ (d 3 ) layers. Ca2 Fe1.1 Mn0.9 O6 exhibits charge disproportionation and magneto‐resistivity. Electron hopping through double‐exchange ferromagnetic interactions between Fe 4+ and Mn 4+ is proposed.